The impact of the elements of accounting information of selected Islamic banks in Bangladesh: Elements of accounting information of selected Islamic banks (IIUC Business Review, 2026)
The elements of accounting information systems (AIS) are essential tools for decision making. The main objective of the study is to evaluate the impact of AIS on the financial information (FI) on selected Islamic banks in Bangladesh. Primary data has been used for analysis, and data are being collected through the questionnaire interview. The study finds out the significant positive correlation between FI and elements of AIS. The study suggests more awareness of AIS and the application of IAS in selected Islamic banks. The management of Islamic banks should arrange more training programme, symposium and seminar for AIS. Policy makers like ICAB and ICMAB should come forward to provide instructions regarding AIS in preparing various record books as well as financial statements by selected Islamic banks in Bangladesh.IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 47-60